Decoding colorectal cancer targeted therapy: a bibliometric journey of the last decade (2015–2024) - Linpo Zhou; Xuanwei Huang; Jing Shi; Yebin Yang; Fanhe Dong; Haoran Wei; Chenghao Ji; Yuqiang Shan (Discover Oncology)
Abstract Colorectal cancer remains one of the most commonly diagnosed cancers globally, with a significant impact on public health. Targeted therapies have revolutionized the treatment landscape for colorectal cancer by offering increased specificity and reduced systemic toxicity compared to conventional chemotherapy. This study provides a comprehensive bibliometric analysis of global research on targeted therapy for colorectal cancer, focusing on publications from 2015 to 2024. A total of 3213 publications were retrieved from the Web of Science Core Collection and analyzed using bibliometric tools to construct knowledge maps and visualize research trends. The regression analysis shows a strong upward trend in publications from 2015 to 2024 (P < 0.001, R2 = 0.889). China leads in publication output, with the University of Texas MD Anderson Cancer Center contributing the highest number of studies. Tabernero and Kopetz are the core authors in the field. Research in this domain has primarily concentrated on the development and clinical assessment of drugs targeting the EGFR, RAS, VEGF, and BRAF signaling pathways, as well as investigating the pathogenesis, drug resistance, and metastatic mechanisms of colorectal cancer. Current advancements emphasize Artificial Intelligence-driven multi-omics integration, the creation of novel therapeutics targeting established molecular pathways, and the execution of global clinical trials to validate personalized treatment strategies.